“Assembling Reminders for a Particular Purpose”: The Nature and Dimensions of Educational Theory - Kazepides, Tasos (Canadian Journal of Education/Revue canadienne de l'éducation, 1994)
This article should be read as prolegomena to the development of a Theory of Education. In it I argue that the term “educational theory” is multiply ambiguous as it may refer to a theory of schooling (which is a non-starter), to a theory of education (which is general and philosophical in nature), or to theories in education (which are specific and empiri- cal). The article points out the logical primacy of a theory of education in the context of which we ought to develop specific theories in education. It emphasizes the importance of a clear and defensible concept of education for educational theory and practice and argues against the view that education is some kind of activity or process. Cet article présente les prolégomènes à une théorie de l’éducation. L’auteur soutient que l’expression “théorie educative” est ambiguë à plus d’un titre, car elle peut être comprise dans le sens d’une théorie de la scolarisation (qui normalement doit venir après une théorie plus générale), ou d’une théorie de l’éducation (qui est de nature générale et philosophique), ou de théories sur l’éducation (qui sont plus circonscrites et empiriques). Dans cet article, l’auteur met en évidence la primauté logique d’une théorie de l’éducation dans le contexte de laquelle devraient s’édifier des théories précises sur l’éducation. Il souligne en outre l’importance d’un concept clair et justifiable de l’éducation pour une théorie et une pratique éducatives, et s’oppose à l’idée que l’éducation est une sorte d’activité ou de processus.